Represas y mercados: Ríos y energía eléctrica en Chile - Bauer, Carl (Revista de Derecho Ambiental, 2016)
How are river systems governed under market-oriented water and electricity policies? How are competing water and energy uses coordinated in a context of markets and privatization? I answer the questions by studying hydropower in Chile as an example of the water-energy nexus: that is, analyzing hydropower along the two different axes of water law and electricity law. Chile is a world leader in applying neoliberal policies in both water and electricity sectors, and the national electricity system depends heavily on hydropower. Because hydropower is both a use of water and a source of electricity, it plays a different yet essential role in each sector. Hydropower dams are governed by both water and electricity laws, but the two laws treat water differently and value it for different purposes. I conclude that Chilean electricity law has granted de facto property rights to water to the owners of hydropower development. This situation is bad news for water sustainability and governance. In the context of climate change, the interactions between water and energy are more complex and critical tea in the past, and we need more studies of hydropower’s dual roles in the two systems.